2018
DOI: 10.18632/aging.101527
|View full text |Cite
|
Sign up to set email alerts
|

Remote ischemic conditioning: a promising therapeutic intervention for multi-organ protection

Abstract: Despite decades of formidable exploration, multi-organ ischemia-reperfusion injury (IRI) encountered, particularly amongst elderly patients with clinical scenarios, such as age-related arteriosclerotic vascular disease, heart surgery and organ transplantation, is still an unsettled conundrum that besets clinicians. Remote ischemic conditioning (RIC), delivered via transient, repetitive noninvasive IR interventions to distant organs or tissues, is regarded as an innovative approach against IRI. Based on the ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 242 publications
0
65
0
Order By: Relevance
“…Remote ischemic conditioning strategy has been suggested to treat both acute ischemic stroke and intracranial atherosclerosis (ICAS) . Our previous study indicated that RIC reduced the incidence of stroke recurrence in ICAS patients from 26.7% to 7.9% after 300 days continuous intervention .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remote ischemic conditioning strategy has been suggested to treat both acute ischemic stroke and intracranial atherosclerosis (ICAS) . Our previous study indicated that RIC reduced the incidence of stroke recurrence in ICAS patients from 26.7% to 7.9% after 300 days continuous intervention .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, remote ischemic conditioning (RIC) has garnered great attention due to its efficacious therapeutic benefit on atherosclerotic intracranial arterial stenosis (ICAS) . It has been demonstrated that RIC can increase the tolerance to cerebral ischemia, reduce stroke recurrence, improve cerebral perfusion, and promote compensatory collateral network formation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protection of at-risk population from acute kidney injury has attracted considerable attention, but the practical outcome to date has been rather limited. A possibility to pre-condition kidney to ischemia by transient ischemic treatment of remote organs is considered as a non-pharmacological measure [33]. However, clinical results for this technique vary considerably between studies [34][35][36], perhaps reflecting the need for further optimization of the procedure, as well as the differences in the study populations [37].…”
Section: Discussionmentioning
confidence: 99%
“…To ensure rigor, we quantified postischemic retinal function by electroretinography in large cohorts. Repetitive systemic hypoxia, which has a human correlate in remote limb conditioning (25), served as the epigenetic conditioning stimulus. We also interrogated the intergenerational neuroprotective phenotype by quantitative mass spectrometry of retinae from F1 mice derived from conditioned and nonconditioned parents.…”
Section: Introductionmentioning
confidence: 99%